Body Image Perception and Eating Disorder Risks: Unexpected Patterns among Female University Students in Botswana - Khumalo, Thembelihle Cacilda; Prachansuwan, Aree; Sahasakul, Yuraporn; Tapanee, Pradtana (Journal of Nutrition Association of Thailand (Online), 2025)
Body image perception plays a complex role in the development of eating disorder risks among female university students in Botswana. Increasing concerns over body image dissatisfaction, especially unexpected patterns such as negative body image among individuals with a normal body mass index (BMI), motivated this study. The research aims to understand better the potential links between body image perceptions and disordered eating behaviors within this population. A total of 328 female students residing on campus at the University of Botswana participated in the study. Data were collected using a self-administered questionnaire, which included the Stunkard Figure Rating Scale to assess body image perception and the Eating Disorder Examination Questionnaire (EDE-Q) to evaluate eating disorder risks. A total of 59.5% of participants reported negative body image perceptions, and 27.4% were identified as being at risk for eating disorders. Among those at risk, 21.5% also exhibited negative body image. Notably, 42.1% of students with a normal BMI perceived their body image negatively. Interestingly, students with a positive body image were found to have a higher likelihood of eating disorder risk, with a relative risk of 1.725 (p = 0.041). Analysis of the EDE-Q subscales revealed elevated concerns related to shape and weight, with mean scores of 2.160 and 1.982, respectively. The overall EDE-Q mean score was 1.61, indicating a slight but notable level of concern regarding the risk of eating disorders among the participants. Although body image dissatisfaction predicted disordered eating behaviors, this study also revealed an unexpected association between positive body image and elevated eating-disorder risk among female students in Botswana. The mean overall EDE-Q score was 1.61 (±1.20), indicating a slight level of concern regarding eating-disorder risk. Participants with positive body image were more likely to exhibit eating-disorder risk (RR = 1.725, 95% CI: 1.022–2.909, p = 0.041). These findings underscore the complex relationship between perceived body satisfaction and disordered eating within this population. Unexpected trends, such as negative body image among normal-weight students and the complex association between positive body image and eating disorder risk, highlight the need for further research and targeted interventions in university settings.